Association Between Circulating Linoleic Acid and Risk of Ischemic Stroke - Ye, Ding; Huang, Huijun; Wu, David J. H.; Zhang, Wanting; Zhou, Feixiang; Qian, Yu; Zheng, Jusheng; Mao, Yingying (Frontiers in Genetics, 2021)
Background: Observational studies have shown an inverse association between circulating linoleic acid (LA) and risk of ischemic stroke (IS). Objective: The aim of this study was to explore whether genetic variants predicting levels of circulating LA are associated with IS and its subtypes using a two-sample Mendelian randomization (MR) analysis. Methods: LA-related single-nucleotide polymorphisms (SNPs) were selected from a genome-wide association study of 8,631 participants, and summary statistics of IS and IS subtypes were obtained from the MEGASTROKE consortium. MR analysis was performed using the inverse-variance weighted (IVW) method complemented with other approaches, including weighted-median, weighted-mode, MR Pleiotropy RESidual Sum and Outlier test (PRESSO) and MR-Egger regression, to test for the robustness of the association. Moreover, we conducted bidirectional MR analysis to assess the impact of IS-associated SNPs on circulating LA levels. Odds ratios (ORs) with 95% confidence intervals (95% CIs) were calculated. Results: We found that genetically predicted circulating LA levels were inversely associated with the risk of IS by the IVW method (OR=0.98, 95% CI: 0.97-0.99, P = 0.003). Subgroup analyses showed a statistically significant association between LA and risk of large artery stroke (LAS) (OR = 0.95, 95% CI: 0.92-0.98, P = 0.004), but not for other IS subtypes. The results were stable in sensitivity analyses, and no evidence of reverse association between LA and risk of IS, or LAS was observed. Conclusions: Our study supports a potential inverse association of genetically predicted circulating LA levels with risk of IS, particularly LAS.